Improving the quality of health care: using international collaboration to inform guideline programmes by founding the Guidelines International Network (G-I-N). Issue 6 (2nd December 2004) - Ollenschläger, G; Marshall, C; Qureshi, S; Rosenbrand, K; Burgers, J; Mäkelä, M; Slutsky, J
Abstract : Clinical practice guidelines are regarded as powerful tools to achieve effective health care. Although many countries have built up experience in the development, appraisal, and implementation of guidelines, until recently there has been no established forum for collaboration at an international level. As a result, in different countries seeking similar goals and using similar strategies, efforts have been unnecessarily duplicated and opportunities for harmonisation lost because of the lack of a supporting organisational framework. This triggered a proposal in 2001 for an international guidelines network built on existing partnerships. A baseline survey confirmed a strong demand for such an entity. A multinational group of guideline experts initiated the development of a non-profit organisation aimed at promotion of systematic guideline development and implementation. The Guidelines International Network (G-I-N) was founded in November 2002. One year later the Network released the International Guideline Library, a searchable database which now contains more than 2000 guideline resources including published guidelines, guidelines under development, "guidelines for guidelines", training materials, and patient information tools. By June 2004, 52 organisations from 27 countries had joined the network including institutions from Oceania, North America, and Europe, and WHO. This paper describes the process that led to the foundation of the G-I-N, its characteristics, prime activities, and ideas on future projects and collaboration.